1991
DOI: 10.1128/mcb.11.1.108
|View full text |Cite
|
Sign up to set email alerts
|

Heparin and hormonal regulation of mRNA synthesis and abundance of autocrine growth factors: relevance to clonal growth of tumors.

Abstract: Highly sulfated, heparinlike species of heparan sulfate proteoglycans, with heparinlike glycosaminoglycan chains, are extracellular matrix components that are plasma membrane bound in growth-arrested liver cells. Heparins were found to inhibit the growth and lower the clonal growth efficiency of HepG2, a minimally deviant, human hepatoma cell line. Heparan sulfates, closely related glycosaminoglycans present in the extracellular matrix around growing liver cells, had no effect on the growth rate or clonal grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…We first examined whether the adipogenesis-blocking chemicals impair the viability of human hepatocellular carcinoma cells that overexpress IGF2, a member of IGFs that is often produced at high levels in liver tumors (27). We identified three chemically analogous compounds that killed IGF2-overexpressing hepatocellular carcinoma cells (Hep-G2) but had milder effects on the cell line with low levels of IGF2 (SK-Hep-1) (28). Repeated experiments with three additional human hepatocellular carcinoma cell lines that we recently characterized 2 indicated that one of the three chemicals, 94G6, exhibited the highest cytotoxicity to IGF2-producing hepatocellular carcinoma cells with selectivity similar to that of a neutralizing antibody against IGF2 (Fig.…”
Section: Figmentioning
confidence: 99%
“…We first examined whether the adipogenesis-blocking chemicals impair the viability of human hepatocellular carcinoma cells that overexpress IGF2, a member of IGFs that is often produced at high levels in liver tumors (27). We identified three chemically analogous compounds that killed IGF2-overexpressing hepatocellular carcinoma cells (Hep-G2) but had milder effects on the cell line with low levels of IGF2 (SK-Hep-1) (28). Repeated experiments with three additional human hepatocellular carcinoma cell lines that we recently characterized 2 indicated that one of the three chemicals, 94G6, exhibited the highest cytotoxicity to IGF2-producing hepatocellular carcinoma cells with selectivity similar to that of a neutralizing antibody against IGF2 (Fig.…”
Section: Figmentioning
confidence: 99%
“…3 Heparin chains affected proliferation by transcriptionally inducing differentiation factors and inhibitory growth factors in the nonmetastatic cells. 4 Previously,we used human colorectal cancer cell lines to assess the role of liver ECM in regulating cell proliferation and found that hepatocyte-derived ECM stimulated the growth of cells that metastasize to the liver. 5 Enhancement of cell proliferation was accompanied by increased amounts of erb-B2 and erb-B3 in the colon cancer cells.…”
mentioning
confidence: 99%
“…3,[6][7][8][26][27][28][29][30][31] Freshly isolated rat hepatocytes can bind to collagen via ␣ 1 ␤ 1 -integrin, 32 as shown by the ability of a monoclonal antibody to the ␣ 1 subunit to block binding to native type I collagen. 33 Hepatocyte binding to fibronectin, specifically at the amino acid sequence RGD, is mediated by ␣ 5 ␤ 1 -integrin.…”
mentioning
confidence: 99%